(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The data on fingins and distribution of one liverwort species (Marchantiophyta) and 20 moss species (Bryophyta)on 3 sandy massives in Pivdenny Bug river flood-plainare given in the article. Cosmopolite species with wide econiche, helads and pioneer species of movable sandy substrates predominate in the bryoflora.